Experimental Evaluation of Ultrasound Influence on Productivity and Quality of Diamond Finishing of Fragile Materials - M. G. Kiselev; V. P. Lugovoy; Farzam Hejazi (Наука и техника)
The paper gives main principles of the methodology for execution of experimental investigations with the help of principally newly designed ultrasound machine-tool with acoustic system which is set in the spindle unit. Treatment of a number of semi-precious stones and mono-crystals by diamond tools of various graininess has revealed dominating technological factors that influence on quantitative and qualitative process indice. Mechanisms of inter-relation of a lapping disk and a treated piece with directed action of ultrasound oscillation are given in the paper. The obtained results testify efficiency of ultrasound application for treatment of hard and fragile materials (crystals).